THE ADOPTION OF THE INTERNATIONAL FINANCIAL REPORTING STANDARDS IN PORTUGAL: CAN EXPECTED COSTS BE REDUCED? - Alves, Paulo A. P.; Moreira, José A. C. (Revista Universo Contábil, 2009)
In this paper we use a cost-benefit framework to discuss some of the expected effects related to the Portuguese adoption of the International Financial Reporting Standards (IFRS). Given the circumstances underlying this implementation, we anticipate that the overall net result following an analysis of costs and benefits will be negative. Therefore, we also examine what seems to be the causal factor behind this outcome and a potential way of reducing the net cost of adopting the IFRS. The costs are related to the professional updating of accounting skills of those directly or indirectly involved in the accounting process. A part of these costs will be incremental and permanent over time mainly due to the fact that two accounting systems will be kept in place. The adoption of a single accounting system, that based on the IFRS, would appear to be a possible solution to reduce such costs.